KAJIAN PENGGUNAAN PENGKELAT UNTUK MENURUNKAN KANDUNGAN BESI DALAM MINYAK DAUN CENGKEH - Saputri, Fatma; Razak, Abd. Rahman; Musafira, Musafira (Univ. Tadulako, 2014)
The investigation about study of the use of chelating agent to reduce iron content in clove oil has been done. This study aimed to determine the type of chelating agent that has the best ability in reducing the iron content in clove oil and to determine the optimum concentration of the chosen chelating agent in reducing the iron content in clove oil. Determination of iron content (Fe) was conducted using Atomic Absorption Spectrophotometry (AAS). The result obtained show that the type of chelating agent that has the best ability in reducing the iron content in clove oil was EDTA with 1,8% of the optimum concentration. It could reduced the iron content from 3,75 ppm to 0,625 ppm or approximately 83,333% of iron reduction.